“Marica”: A Story-Based Motion-Comic Learning Media to Improve Students’ Mathematical Representation - Chrisnawati, Henny Ekana; Pinilih, Anggoro Canggih; Nurhasanah, Farida; Usodo, Budi; Sutopo, Sutopo; Kuswardi, Yemi (FKIP Universitas Lampung, 2024)
Abstract: